Diagnóstico da gestão de projetos de pesquisa acadêmica: um estudo de dois casos da ufmg - Rafael Mizerani Couto Moreira (2018)
Through research results the university has a role of inducing innovation development according to the Triple Helix concept. In the last years some authors have shown project management as the new scientific research paradigm. This management must be done in an environment of extreme uncertainty, resources scarcity and a high-level need of autonomy and flexibility. In this context, traditional, also called predictive, project management may not produce good results. As an alternative new project management approaches have emerged, adaptative and agile. With the objective of diagnose how project management practices fit to academic research, an multiple case study was conducted in the UFMG. By the contrast between them and the literature, an hybrid approach is pointed to fit nowadays research environment. Some implications of this results are the employment of a full stack manager to handle laboratory infrastructure and let researches free to do their work, the need of training the manager-research over the practices and a possible improvement in the relationship between university and industry, starting with the learning about academic project management context and the adoption of a common language